194k views
5 votes
Try the following example. Remember to use the hints if you need them. Solve for x. 2.9×10−7=(x)(x)2(4.6)(4.6)2(3)2 Choose the correct answer. View Available Hint(s) Choose the correct answer. 4.0×10−6 2.3 2.3×10−2 I don’t know. I am unable to obtain any of the answers but I do not want to give up.

1 Answer

5 votes

Answer:


2.3* 10^(-2)

Explanation:

Given equation,


2.9* 10^(-7)=((x)(x)^2(4.6))/((4.6)^2(3)^2)


2.9* 10^(-7)=(x^3)/(9* 4.6)


(\because a^m = (1)/(a^(-m)))

By cross multiplication,


2.9* 9* 4.6* 10^(-7)=x^3


120.06* 10^(-7)=x^3


\implies x = (120.06* 10^(-7))^(1)/(3)


=0.0228980999294


\approx 0.023


=2.3* 10^(-2)

User Pathmapper
by
5.2k points